Design and manufacture of high performance hollow engine valves by Additive Layer Manufacturing. (15th March 2015) - Cooper, D.; Thornby, J.; Blundell, N.; Henrys, R.; Williams, M.A.; Gibbons, G.
Highlights: High performance engine valve has been redesigned and optimised for and using ALM. FEA was utilised to optimise and select a design for manufacture and testing. Micro computed tomography was used in design and validation as an NDT technique. Real world test of components was conducted to evaluate their performance. Has demonstrated the potential for ALM in a high performance engineering context. Abstract: Additive Layer Manufacture (ALM) of metallic components provides significant opportunities for the reduction of component weight, in order to realise improvements in vehicle fuel efficiency or performance. This paper examines the potential benefits of ALM with regard to reducing the weight of Internal Combustion Engine inlet or exhaust valves. A case study component is presented, for which an improved ALM design has been created, manufactured and evaluated. Micro-Computed Tomography (μ-CT) scanning was utilised to reverse engineer an original component, and to assess the ALM component's internal geometry and material integrity. The case study valve was re-designed using Finite Element Analysis (FEA) to select a light weighted design which provides a conservative 9.4 g, (20%) weight saving on the Original Equipment Manufacturer (OEM) component. An engine test of over 175, 000 cycles at between 2000 and 9500 rpm was conducted, after which μ-CT scanning confirmed no evidence of internal cracking, failure or significant deformation.